Analysis of Safety Management System Implementation and Occupational Health Based on PP No 50 Year 2012 - Eka Rakhmat Kabul; Subhan Nur Ramadhan; Sukiman Sukiman; Harries Madiistriyatno (Eduvest - Journal of Universal Studies, 2022)
This research aims to know the implementation of Occupational Health and Safety Management System which is implemented in RSUD Karawang. Research Methods: Qualitative Research, descriptive type. The sampling technique used by the researcher is purposive sample. Samples were taken as many as 3 employees of RSUD Karawang as respondents in this study. Result : Leadership commitments and policies towards the implementation of K3 already exist and in writing, the facilities and infrastructure that support the implementation of K3 have been fulfilled. While the K3 policy at this hospital is the appointment of the K3 Installation as an officer who oversees the implementation of K3 at the Karawang Hospital, the K3 Planning at the Karawang Hospital has been going well starting from risk identification to risk management. In addition, workers are also required to follow SOPs every time they do their work, and workers have been facilitated with complete PPE by the hospital. The organization has formed an organization for the K3RS Installation but it is still found that the workers from the K3 installation have double jobs where the implementation of the SMK3 program is not optimal. The implementation of OSH, most of the steps for implementing SMK3 have been going well at the Karawang Hospital where the Hospital has stated a commitment, an OHS organization has been formed, conducting K3 counseling to workers, implementing K3 programs such as providing PPE, health checks, and treating sick workers with provide BPJS services. The audit at the Karawang Hospital has been running, where internal and external audits have been running to find out what are the shortcomings of the K3 program and further correct the shortcomings of the K3 program aimed at improving the K3 program.